Comparison of machine learning models to predict the risk of breast cancer-related lymphedema among breast cancer survivors: a cross-sectional study in China - Du, Jiali; Yang, Jing; Yang, Qing; Zhang, Xin; Yuan, Ling; Fu, Bing (Frontiers in Oncology, 2024)
Objective The aim of this study was to develop and validate a series of breast cancer-related lymphoedema risk prediction models using machine learning algorithms for early identification of high-risk individuals to reduce the incidence of postoperative breast cancer lymphoedema.This was a retrospectivel study conducted from January 2012-July 2022 in a tertiary oncology hospital. Subsequent to the collection of clinical data, variables with predictive capacity for Breast Cancer-related Lymphoedema (BCRL) were subjected to scrutiny utilizing the least absolute shrinkage and selection operator (LASSO) technique.The entire dataset underwent a randomized partition into training and test subsets, adhering to a 7:3 distribution. Nine classification models were developed, and the model performance was evaluated based on accuracy, sensitivity, specificity, recall, precision, F-score , and Area Under Curve (AUC) of the ROC curve.Ultimately, the selection of the optimal model hinged upon the AUC value.Grid search and ten-fold cross-validation was used to determine the best parameter setting for each algorithm.Results A total of 670 patients were investigated, of which 469 were in the modelling group and 201 in the validation group. A total of 174 had BCRL (25.97%).The LASSO regression model screened for the 13 features most valuable in predicting BCRL. The range of each metric in the test set for the nine models was, in order: accuracy (0.75-0.84), sensitivity (0.50-0.79), specificity (0.79-0.93), recall (0.50-0.79), precision (0.51-0.70 ), F score (0.56-0.69), and AUC value (0.71-0.87). Overall, LR achieved the best performance in terms of accuracy (0.81), precision (0.60), sensitivity (0.79), specificity (0.82), recall (0.79), F-score (0.68), and AUC value (0.87) for predicting BCRL.The study established that the constructed Logistic Regression (LR) model exhibits a more favorable amalgamation of accuracy, sensitivity, specificity, recall and AUC value. This configuration adeptly discerns patients who are at an elevated risk of BCRL. Consequently, this precise identification equips nurses with the means to undertake timely and tailored interventions, thus averting the onset of BCRL.